Capital Formation, Economic Growth, and Unemployment in India: A Causality Effects Analysis - Kumar Sinha, Jitendra; Anurodh Kumar Sinha (Journal of Advanced Research in Economics and Business Management, 2022)
Indian economy faces a higher rate of unemployment despite the moderate rate of investment and economic growth. Gross Capital Formation is designed to improve employment and economic growth. This study investigated within the framework of the Vector Error Correction Model (VECM) the nature of investment, economic growth, and employment in India during the post-economic reform period (1990- 2021). The results show that a long-run relationship exists between these variables. It also suggests a piece of evidence in favor of bi-directional causality between employment and economic growth. Investments do not precede economic growth. Rather economic growth is found to precede investment, i.e., economic growth attracts investment, which leads to employment in the long run in the Indian situation. The study also confirms the hypothesis of jobless growth in the post-economic reform period. It also suggests that a favorable economic environment needs to be vigorously pursued through improved infrastructural acilities, and diversification of the economy in the labor-intensive sectors like agricultural and allied sectors to spur investment level in the country.